2017
DOI: 10.3390/w9070540
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Hydrological Response to Rainfall at Multi Spatio-Temporal Scales in Savannas of Semi-Arid Australia

Abstract: Abstract:Rainfall is the main driver of hydrological processes in dryland environments and characterising the rainfall variability and processes of runoff generation are critical for understanding ecosystem function of catchments. Using remote sensing and in situ data sets, we assess the spatial and temporal variability of the rainfall, rainfall-runoff response, and effects on runoff coefficients of antecedent soil moisture and ground cover at different spatial scales. This analysis was undertaken in the Upper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 58 publications
(95 reference statements)
1
18
1
Order By: Relevance
“…Relationships between indicators of AMC and flow activation times were weaker, compared with those with rainfall intensity. Although several studies in semiarid areas have reported strong relationships between AMC and OF characteristics in general (e.g., Brocca, Melone, & Moramarco, ; Li & Chibber, ) as well as seasonally (e.g., Castillo et al, ; Jarihani, Sidle, Bartley, Roth, & Wilkinson, ), such was not consistently the case here. This is likely because OF occurred primarily as HOF at our site.…”
Section: Discussioncontrasting
confidence: 75%
“…Relationships between indicators of AMC and flow activation times were weaker, compared with those with rainfall intensity. Although several studies in semiarid areas have reported strong relationships between AMC and OF characteristics in general (e.g., Brocca, Melone, & Moramarco, ; Li & Chibber, ) as well as seasonally (e.g., Castillo et al, ; Jarihani, Sidle, Bartley, Roth, & Wilkinson, ), such was not consistently the case here. This is likely because OF occurred primarily as HOF at our site.…”
Section: Discussioncontrasting
confidence: 75%
“…The climate is dry-tropical with two distinct seasons; a summer wet season between October and March, and a dry season between April and September [86]. The mean-annual rainfall (1900-2012) is 686 mm year −1 , but exhibits high interannual variability linked to the phase of the Southern Oscillation, with drought conditions coinciding with El Niño/Southern Oscillation (ENSO), and wetter periods accompanying anti-ENSO (La Niña) events [87,88]. Vegetation is generally characterised by a discontinuous upper stratum of Eucalyptus spp.…”
Section: Study Sitementioning
confidence: 99%
“…conditions coinciding with El Niño/Southern Oscillation (ENSO), and wetter periods accompanying anti-ENSO (La Niña) events [87,88]. Vegetation is generally characterised by a discontinuous upper stratum of Eucalyptus spp.…”
Section: Study Sitementioning
confidence: 99%
“…Overall, results showed that for both catchments, including rainfall of the previous months increased model accuracy compared to just using rainfall of the same month. This shows the importance of antecedent soil moisture in the runoff generation process [68]. Additionally, including runoff and rainfall together as input data slightly improved model performance for both catchments ( Table 4), indicating that only using rainfall is insufficient to precisely estimate runoff, while combining this with antecedent runoff improves predictions [59].…”
Section: Different Patterns Of Hydro-climate Datamentioning
confidence: 88%